Topical administration of red ginger (Zingiber officinale Rosc) extract gel increased the number of fibroblast, neovascularization, and epitelization of wound healing in old male mice (Mus musculus) - Hayyu Kusumaningtyas; I Gusti Made Aman; Ida Sri Iswari (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Wound healing is slower with advancing age. Red ginger extract is a natural compound that contains flavonoids and polyphenols. This study aims to prove that the topical administration of red ginger (Zingiber officinale Rosc) extract gel increases the number of fibroblasts, neovascularization, and epithelialization of wound healing in old male mice (Mus musculus). Methods: This study was an experimental study using randomized posttest only control group design using 32 male mice, aged 12 months, weighing 20 grams, which was divided randomly into 2 groups. The control and treatment group was further divided into 4-day group and 8-day group. The control group was applied with placebo gel twice a day and given oral amoxicillin for three days (3 times a day) in the wound site, while the treatment group was applied with 30% red ginger extract gel twice a day and given oral amoxicillin. Results: The average number of neovascularization in the fourth day of the control group was 31.37±3.98, while in the treatment group was 68.17±11.56 (p< 0.001). The average number of fibroblasts on the fourth day of the control group was 77.04±5.57, and in the treatment group was 103.99±10.68 (p< 0.001). On the fourth day there was no epithelialization observed, and on the eight day the mean epithelialization in the control group observed was 30.35±6.01 μm, while in the treatment group was 78.25±18.26 μm (p<0,001). Conclusion: Topical administration of red ginger extract gel increased the number of fibroblasts, neovascularization, and epithelialization of wound healing in old male mice.